Implementasi Pengelolaan Emisi Pabrik Semen Menggunakan Subtitusi Batubara-Limbah B3 Dan Dampak Kesehatan Masyarakat Menggunakan Aermod-Ahp - Purnama, Elanda Reinelda; Hermana , Joni (Syntax Corporation, 2025)
The cement industry is important in infrastructure development but significantly pollutes the air due to coal emissions. This study evaluates emissions from chimneys of cement factories that use B3 waste as an alternative fuel. The AERMOD dispersion model is used to predict PM10, NO₂, SO₂, and CO concentrations. The Analytic Hierarchy Process (AHP) method determines the priority of mitigation strategies based on pollutant concentration, exposure intensity, and disease prevalence. Primary and secondary data were collected over a period of one year that included plant operational parameters, meteorological conditions, and surrounding public health data. The results showed that the use of AERMOD software was effective in identifying areas with the highest concentrations of pollutants, allowing for the implementation of targeted mitigation strategies. Health risk analysis using the Dose Response Function (DRF) approach showed that the highest change in health risk due to CO pollutants reached 293.8 cases in the dry season, while NO₂ reached 180.8 cases in the same season. The use of substitute fuels significantly reduced changes in health risks, with CO becoming 146.9 cases in the wet season and doubling to 293.8 cases in the dry season, and NO₂ only about 2 cases. Analysis using AHP showed that increasing green areas (weight 0.298) and applying pollution control technology (weight 0.267) were the most effective mitigation strategies. Health mitigation programs (weight 0.253) are also prioritized to reduce the prevalence of diseases related to air pollution. The findings of this study contribute to improving air quality and public health and support the use of more sustainable alternative technologies and fuels.